2009
DOI: 10.3233/ch-2009-1239
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological changes in cerebral circulation of rabbits with acute carbon monoxide poisoning

Abstract: Carbon monoxide (CO) poisoning is a leading cause of poison-related morbidity and mortality. The severe complication of delayed neuropsychiatric sequelae seriously affects patient's living quality, but its mechanism remains controversial. In this study, we established an animal model by intraperitoneal injection of CO in rabbits at regular interval and kept the carboxyhemoglobin (HbCO) level in blood above 50% for at least 24 h. We investigated the dynamic changes in the hemorheological and coagulative propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The widely accepted view is that the increase in blood flow may be able to supply enough oxygen so that there is no change in the oxygen consumption. Another interpretation is that the increase in blood flow may cause vasodilation independently based upon oxygen level with dilatory agent (such as NO) and maintain adequate tissue oxygen level with the increased oxygen extraction [ 40 ]. But the change in whole blood viscosity at low shear rate occurring on day 1 after CO exposure could have disturbed the microcirculation in brain, especially in the regions with poor vasculatures, such as white matter, globus pallidus, basal ganglia, and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The widely accepted view is that the increase in blood flow may be able to supply enough oxygen so that there is no change in the oxygen consumption. Another interpretation is that the increase in blood flow may cause vasodilation independently based upon oxygen level with dilatory agent (such as NO) and maintain adequate tissue oxygen level with the increased oxygen extraction [ 40 ]. But the change in whole blood viscosity at low shear rate occurring on day 1 after CO exposure could have disturbed the microcirculation in brain, especially in the regions with poor vasculatures, such as white matter, globus pallidus, basal ganglia, and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] It is reported that lung injury, including thickening of the alveolar-capillary membrane, degeneration in alveoli, alveolar congestion, hamorrhage, neutrophil infiltration or aggregations and so on, does occur in AOPP. 7 Recent studies indicated that mechanisms other than AChE inhibition may be involved in the progression of AOPP, including oxidative stress, mitochondrial energy metabolism impairment, 8,9 microcirculation disturbance, [10][11][12] and acute inflammation. [13][14][15] Escin is one of the main bioactive constituents of Aesculus hippocastanum, which is a plant distributed all over the world because of its excellent resistance to environmental conditions.…”
Section: Introductionmentioning
confidence: 99%